Food Fortification in the Philippines - Saleh, Nadira (The Meducator, 2012)
Many of the world’s poorest are suffering from what is known as “hidden hunger”: deficiencies of proper vitamins and minerals. The Philippines is considered a model in its comprehensive interventions, especially in food fortification. Through investigation of this model, its achievements and its shortcomings, other countries may also be able to better nourish their citizens.